Towards understanding of pore properties of polystyrene-b-polybutadiene-b-polystyrene (SEBS) foam effect on thermal conductivity using numerical analysis - Muhammad Zulkarnain; Sharudin, Rahida Wati; Ohshima, Masahiro (Universitas Indonesia, 2022)
Thermoplastic elastomer Polystyrene-b-polybutadiene-b polystyrene (SEBS) foams are prepared by using carbon dioxide (CO2) as a blowing agent via a pressure quench method. During the foaming process, various pore shapes are developed inside the foam, which is influenced by several parameters such as rigidity, solubility, and diffusivity of CO2. A previous study revealed the theory of how SEBS foams may shrink due to low rigidity and high CO2 diffusivity, but empirical verification on how the final cell properties like cell shape, cell size, cell distribution, and percentage of porosity may affect the thermal conductivity of SEBS foam is challenging to represent experimentally. This is due to difficulty in preparing foam samples at different cell shapes for the same polymer, different percentages of porosity, and cell distribution while keeping the same cell size of the SEBS foam. This paper discussed how numerical analysis is employed to investigate various properties of pores such as cell shape, cell size, cell distribution, and percentage of porosity on the thermal conductivity. The simulation results are corroborated with experimental value where the reduction of thermal conductivity is observed with a higher percentage of porosity which is shown by all cell shapes foam such as spherical, ellipse, and irregular.